Decreased Expression of the EAAT5 Glutamate Transporter at Photoreceptor Synapses in Early, Pre-Clinical Experimental Autoimmune Encephalomyelitis, a Mouse Model of Multiple Sclerosis - Ali El Samad; Julia Jaffal; Dalia R. Ibrahim; Karin Schwarz; Frank Schmitz (Biomedicines, 2024)
Background: Multiple sclerosis is a frequent neuroinflammatory and neurodegenerative disease of the central nervous system that includes alterations in the white and gray matter of the brain. The visual system is frequently affected in multiple sclerosis. Glutamate excitotoxicity might play a role in disease pathogenesis. Methodology: In the present study, we analyzed with qualitative and quantitative immunofluorescence microscopy and Western blot analyses whether alterations in the EAAT5 (SLC1A7) glutamate transporter could be involved in the previously observed alterations in structure and function of glutamatergic photoreceptor ribbon synapses in the EAE mouse model of MS. EAAT5 is a presynaptic glutamate transporter located near the presynaptic release sites. Results: We found that EAAT5 was strongly reduced at the photoreceptor synapses of EAE retinas in comparison to the photoreceptor synapses of the respective control retinas as early as day 9 post-immunization. The Western blot analyses demonstrated a decreased EAAT5 expression in EAE retinas. Conclusions: Our data illustrate early alterations of the EAAT5 glutamate transporter in the early pre-clinical phase of EAE/MS and suggest an involvement of EAAT5 in the previously observed early synaptic changes at photoreceptor synapses. The precise mechanisms need to be elucidated by future investigations.